Role of Aspartate Aminotransferase to Platelet Ratio Index as a non-invasive predictor of variceal etiology. - Altaf, Hunza; Noreen, Khola; Akbar, Abrar; Mahmud, Muhammad Rizwan; Shahzadi, Kanwal; Meraj, Lubna (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the diagnostic accuracy of the aspartate aminotransferase to Platelet ratio index as an indicator of upper gastrointestinal bleeding, taking endoscopy as the gold standard. Methodology: The cross-sectional validation study was conducted in the Department of Medicine Unit I, Benazir Bhutto Hospital, Rawalpindi, from 25th September 2022 to 24th March 2023. A total of 350 patients aged 16-75 years, both genders, diagnosed with cirrhosis were included. Then a blood sample was taken in a 3cc disposable syringe. Reports were assessed, and APRI was calculated. The patient was labelled as positive or negative. Then the patient underwent upper gastrointestinal endoscopy within 24 hours of admission, and the patient was labelled as positive or negative based on endoscopy findings. Results: Aspartate aminotransferase - Platelet Ratio Index overall sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy as a predictor of upper gastrointestinal bleeding requiring endoscopy were 93.24%, 91.60%, 94.15%, 90.34%, and 92.57%, respectively. Conclusion: The Aspartate Aminotransferase Platelet Ratio Index (APRI) has a fairly high diagnostic accuracy for variceal bleeds.